Analisis Pembiayan Mudharabah Terhadap Peningkatan Usaha Nasabah Priode 2022 (Studi Pada Bsi Kcp Probolinggo Soetta) - Rudi Hartono; Mamluatun Ni’mah; Cici Widya Prasetyandari (Economics and Digital Business Review, 2023)
In the digital era, sharia banking is growing rapidly and has become a reference for the community in managing funds for various aspects of community needs. In this case, the public must understand the various products of BSI (Bank Syariah Indonesia), one of which is applying a mudharabah contract on savings or other products. In this article, the author wants to discuss the analysis of mudharabah financing on increasing customer businesses. Then the research method used is descriptive qualitative, namely by observing and interviewing one of the employees of the Indonesian Islamic Bank (BSI). and fund owners. In this case, the owner of the fund does not place any restrictions on the customer, in order to run the type of business that will be managed, the period of time, and the area of ​​the business does not violate sharia principles and fulfills all aspects and provisions of the bank.